2023
DOI: 10.1021/acsapm.2c02029
|View full text |Cite
|
Sign up to set email alerts
|

Highly Conducting Poly(arylene-imidazolium) Anion Exchange Membranes Containing Thin-Span Channels Constructed by Cation–Dipole Interaction

Abstract: The membrane-based alkaline electrolyzer and fuel cell system has a significant drawback because it uses a concentrated, corrosive alkaline electrolyte. The anion exchange membranes (AEMs) also have lower conductivity than proton exchange membranes (PEMs) because OH − ions have a lower penetration coefficient. In this study, intending to prepare AEMs with high ionic conductivity in low concentrations of alkaline solution, two imidazolium diol monomers have been synthesized as unique candidates for the synthesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…DMSO-d 6 was used as a deuterium substitute reagent. NMR spectra were recorded using 1 H and 19 F NMR (Bruker Avance III spectrometer). The infrared spectra of all samples were obtained with a Bruker Vector 22 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…DMSO-d 6 was used as a deuterium substitute reagent. NMR spectra were recorded using 1 H and 19 F NMR (Bruker Avance III spectrometer). The infrared spectra of all samples were obtained with a Bruker Vector 22 spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, the results of a large number of studies have shown that too many cations will inevitably lead to a significant increase in water absorption and swelling, which inevitably reduces the mechanical properties of the membranes, and therefore, this method is not optimal. Subsequently, inspired by the high performance of Nafion membranes by inducing the generation of polarity differences within the membrane, focusing on the formation of intramembrane microphase-separated structures and the construction of ion transport channels became the preferred choice of researchers to improve ionic conductivity. On the one hand, microphase separation can be induced by designing block, comb, side chain, and ion cluster polymer structures that can self-assemble within the membranes. On the other hand, noncovalent bonding interactions such as hydrogen bonding, Π–Π stacking interactions, and ion–dipole interactions are introduced within the membranes. However, the ion–dipole interaction is the most powerful compared to the other interactions. This strong molecular interaction well promotes intramembrane self-assembly as well as the formation of interconnected ionic network domains, providing a three-dimensional transport pathway for water and ion transport. , Ma et al designed a block polymer structure by introducing –CF 3 groups in the main chain and hydrophilic cations with long alkyl chains in the side chains, thus enhancing the hydrophobicity of the main chains .…”
Section: Introductionmentioning
confidence: 99%
“…Polymer electrolyte fuel cell (PEFC) technology is considered as an environment-friendly energy conversion device to address fuel resource depletion and global warming due to its near-zero pollution and excellent energy conversion efficiency. PEFCs can be classified as proton exchange membrane fuel cells (PEMFCs), which function in acidic conditions, and anion-exchange membrane fuel cells (AEMFCs), which operate in an alkali environment. , PEMFCs have been applied in some fields due to their good fuel cell performances. Nevertheless, the high cost associated with the utilization of perfluorinated membranes and Pt-based catalysts hinders the large-scale commercial application of PEMFCs .…”
Section: Introductionmentioning
confidence: 99%
“…22,23 AEMs have lower ionic conductivity than PEMs due to the lower diffusion coefficient of OH − ions compared to H + ions. 24,25 Increasing the ion exchange capacity, creating nanochannels, 26 and incorporating various quaternary salt groups into the membrane are common strategies to enhance ion conductivity. 13,27 One approach to enhance anion conductivity is to establish unhindered ion-carrying routes with clustered sites that penetrate the inert polymer matrix, creating ion transfer nanochannels.…”
Section: Introductionmentioning
confidence: 99%
“…The anion exchange membrane plays a crucial role in these systems, significantly impacting their efficiency. AEMs are also employed in various applications, including acid recovery by diffusion dialysis (DD), redox flow batteries, reverse electrodialysis, water purification applications, and electrolyzers. Researchers have been interested in developing AEMs that exhibit improved ion conductivity, chemical stability, and mechanical durability for the aforementioned systems. , AEMs have lower ionic conductivity than PEMs due to the lower diffusion coefficient of OH – ions compared to H + ions. , Increasing the ion exchange capacity, creating nanochannels, and incorporating various quaternary salt groups into the membrane are common strategies to enhance ion conductivity. , One approach to enhance anion conductivity is to establish unhindered ion-carrying routes with clustered sites that penetrate the inert polymer matrix, creating ion transfer nanochannels. ,, Lin et al demonstrated improved conductivity at 80 °C (117.5 S cm –1 ) using poly­(terphenylene)-based anion exchange membranes with piperidinium clusters and conductive channels …”
Section: Introductionmentioning
confidence: 99%